2016
DOI: 10.1016/j.neuron.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

A Sensor for Low Environmental Oxygen in the Mouse Main Olfactory Epithelium

Abstract: SummarySensing the level of oxygen in the external and internal environments is essential for survival. Organisms have evolved multiple mechanisms to sense oxygen. No function in oxygen sensing has been attributed to any mammalian olfactory system. Here, we demonstrate that low environmental oxygen directly activates a subpopulation of sensory neurons in the mouse main olfactory epithelium. These neurons express the soluble guanylate cyclase Gucy1b2 and the cation channel Trpc2. Low oxygen induces calcium infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 29 publications
4
63
0
1
Order By: Relevance
“…27d However, it was shown that the human musk-sensitive receptor OR5AN1, expressed in HEK293T cells derived from human embryonic kidney, and identified through screening of 330 similarly expressed human ORs as the sole bona fide receptor for cyclopentadecanone, fails to distinguish a series of deuterated and nondeuterated isotopologues of cyclopentadecanone and other musk odorants. Furthermore, pairs of deuterated and nondeuterated acetophenone, benzaldehyde, and several other deuterated and nondeuterated odorants, and pairs of 13 C and normal isotopologues of both acetophenone and benzaldehyde failed to show differences when tested against their respective, responsive ORs. 30 In addition, contrary to the claim that a musk receptor “detects vibrations in the 1380- to 1550-cm -1 range” where musks are said to have intense bands, 27d it was found that fully deuterated muscone, which strongly activates OR5AN1 equally as well as the undeuterated muscone, is devoid of 1380- to 1550-cm -1 absorption.…”
Section: Theories Of Olfactionmentioning
confidence: 95%
See 2 more Smart Citations
“…27d However, it was shown that the human musk-sensitive receptor OR5AN1, expressed in HEK293T cells derived from human embryonic kidney, and identified through screening of 330 similarly expressed human ORs as the sole bona fide receptor for cyclopentadecanone, fails to distinguish a series of deuterated and nondeuterated isotopologues of cyclopentadecanone and other musk odorants. Furthermore, pairs of deuterated and nondeuterated acetophenone, benzaldehyde, and several other deuterated and nondeuterated odorants, and pairs of 13 C and normal isotopologues of both acetophenone and benzaldehyde failed to show differences when tested against their respective, responsive ORs. 30 In addition, contrary to the claim that a musk receptor “detects vibrations in the 1380- to 1550-cm -1 range” where musks are said to have intense bands, 27d it was found that fully deuterated muscone, which strongly activates OR5AN1 equally as well as the undeuterated muscone, is devoid of 1380- to 1550-cm -1 absorption.…”
Section: Theories Of Olfactionmentioning
confidence: 95%
“…7a Non-GPCR chemosensors and oxygen chemosensors are also known. 13b,c In insect olfaction, not considered here, ORs are mainly located on the antennae and have significantly different structures than their vertebrate counterparts.…”
Section: Introduction: Odorants and The Olfactory Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiological and biochemical studies of olfaction to date offer strong evidence that the majority of mammalian OR signalings are associated with G-protein dependent pathway [7]. Thus, except for a few cases [8,9,10], their activation mechanism is mostly related to that of G-protein coupled receptors (GPCRs) [11,12,13]. Upon binding odorants, a set of ORs adopt their structures into active forms and catalyze G-proteins to initiate downstream signal cascades.…”
Section: Introductionmentioning
confidence: 99%
“…Two subpopulations of OSNs within the MOE also rely on cGMP signaling. One, a subset of OSNs that express the ion channel Trpc2, also contains the soluble guanylyl cyclase Gucy1b2 and the phosphodiesterase Pde6d, and uses cGMP signaling to respond to decreases in environmental O2 (Omura and Mombaerts, 2015;Bleymehl et al, 2016). The second expresses the receptor guanylyl cyclase GC-D (hence their typical designation as GC-D+ OSNs), Cnga3 and Pde2a (Fulle et al, 1995;Juilfs et al, 1997;Meyer et al, 2000).…”
Section: Introductionmentioning
confidence: 99%